Pięć szeregów głosek dentalizowanych? O półpalatalnych głoskach szumiących i ciszących - Myszka, Agniesza (Logopedia Silesiana, 2015)
For a long time linguists and speech therapists have drawn attention to the worrying phenomenon of the common use of the slightly softened articulation of rustling consonants series and the slightly hardened (semi soft) one of hushing consonants series. Its diagnostics – the speech description of (mostly) young people, the assessment of the scale of the phenomenon, the analysis of phonetic and situational conditions of such an articulation and the reflection on the causes of the spread of semi-soft articulation – is the main aim of this paper. Both extra- and intra-lingual causes have been analysed, whereas two other processes – prognostics and anagnostics – have only been indicated. An important question whether it is necessary to correct the semi-palatal articulation does not provide a definite answer, especially since such an articulation does not disturb the communication and is generally unnoticed by the speakers.